The forgotten Luther. - Braaten, Conrad A.; Cumming, Ryan P. (Fortress Press, 2021)
"This study book, the third in the Forgotten Luther series, invites congregations, with the help of five prominent church leaders and Luther scholars, to consider the new shape of global mission in today's world.Against the growing disparity in wealth and the rising tide of economic refugees throughout the world, this book reflects on Luther's largely forgotten social and economic reforms (to overcome poverty, lack of health care, illiteracy, and old-age insecurity) that flowed from the central doctrine of justification by grace through faith. The book is also a call for informed engagement with partner churches in a critical area of ministry that is frequently neglected. This study book draws global implications from Luther's reforms and from the theology that shaped them. It is informed by ways in which churches in the Global South have moved beyond world-denying forms of pietism to address the systemic causes of hunger, poverty, and injustice. It is addressed to the whole church at a critical time in history as vast threats to the natural world converge with acute economic hardship for hundreds of millions of people."--Publisher.